Evidence of efficient stop codon readthrough in four mammalian genes. Issue 14 (10th July 2014) - Loughran, Gary; Chou, Ming-Yuan; Ivanov, Ivaylo P.; Jungreis, Irwin; Kellis, Manolis; Kiran, Anmol M.; Baranov, Pavel V.; Atkins, John F.
Abstract: Stop codon readthrough is used extensively by viruses to expand their gene expression. Until recent discoveries in Drosophila, only a very limited number of readthrough cases in chromosomal genes had been reported. Analysis of conserved protein coding signatures that extend beyond annotated stop codons identified potential stop codon readthrough of four mammalian genes. Here we use a modified targeted bioinformatic approach to identify a further three mammalian readthrough candidates. All seven genes were tested experimentally using reporter constructs transfected into HEK-293T cells. Four displayed efficient stop codon readthrough, and these have UGA immediately followed by CUAG. Comparative genomic analysis revealed that in the four readthrough candidates containing UGA-CUAG, this motif is conserved not only in mammals but throughout vertebrates with the first six of the seven nucleotides being universally conserved. The importance of the CUAG motif was confirmed using a systematic mutagenesis approach. One gene, OPRL1, encoding an opiate receptor, displayed extremely efficient levels of readthrough (∼31%) in HEK-293T cells. Signals both 5′ and 3′ of the OPRL1 stop codon contribute to this high level of readthrough. The sequence UGA-CUA alone can support 1.5% readthrough, underlying its importance.